Revision of the genus Attemsostreptus Verhoeff, 1941 with description of a new species from Tanzania and notes on the tribe Trachystreptini Cook, 1896 (Spirostreptida, Diplopoda) - Akkari, Nesrine; Enghoff, Henrik (European Journal of Taxonomy, 2019)
We revise the genus Attemsostreptus Verhoeff, 1941 based on type material of the type species, A. costatus Verhoeff, 1941, synonymise A. orobius (Kraus 1958) with A. costatus and describe a second species of the genus, A. reflexus sp. nov., collected from Kimboza Forest Reserve in Tanzania, and discuss the dubious tribe Trachystreptini.